EFFECT OF ORGANICS ON MORPHO-PHYSIOLOGICAL TRAITS AND GRAIN YIELD OF MAIZE (ZEA MAYS L.) - VIDYA V. CHOUDHARI; B. B. CHANNAPPAGOUDA (The Bioscan, 2015)
A field experiment was undertaken during Kharif Season 2011 in the Main Agricultural Research Station, University of Agricultural Sciences Dharwad with a view to study the effect of organics on morpho-physiological traits and grain yield of maize (Zea mays L.). Application of organic and inorganic sources of nutrient in combination remarkably increased leaf area, leaf area index, total dry matter and grain yield of maize in alone. Poultry manure @ 1.5 t ha-1 + 100% RDF recorded significantly higher leaf area, leaf area index, total dry matter and grain yield in comparison to other treatments and this was followed by Sheep manure @ 1.87 t ha-1 + 100% RDF. At 60 DAS, Poultry manure @ 1.5 t ha-1 + 100% RDF increased the leaf area (13.50 dm-2 plant-1), leaf area index (4.45) , total dry matter at harvest (292.6 g plant-1) and grain yield (90.2 q/ha) over control. The lowest leaf area, LAI, TDM and grain yield was recorded in control. From the study it can be concluded that combined application of poultry manure @ 1.5 t ha-1 + 100% RDF recorded higher growth parameters and yield of maize.